Purification and biochemical characterization of extracellular thermostable lipase from Bacillus sp. strain L2 - Nezhad, Nima Ghahremani; Mohammed Mukred, Abdul Daim; Raja Abd Rahman, Raja Noor Zaliha; Basri, Mahiran; Salleh, Abu Bakar; Leow, Thean Chor (Springer Science and Business Media Deutschland GmbH, 2024)
In the current study, an extracellular thermostable lipase from Bacillus sp. strain L2 was produced and purified through two-steps purifications, including ammonium sulfate precipitation and Heparin-Sepharose affinity chromatography. Then, the optimum pH, optimum temperature, thermostability, the effect of metal ions and inhibitors, and substrate specificity towards the natural oils were investigated. Extracellular L2 lipase showed a purification fold of 2.74 and specific activity of 3.54 U/mg towards olive oil as substrate. Furthermore, the purified extracellular L2 lipase had the optimum temperature and pH of 80 °C and pH 7, respectively. The half-lives (t1/2) of L2 lipase at 80 and 85 °C were 150 and 13.43 min, respectively. Moreover, the SDS-PAGE analysis illustrated the single band with a molecular mass of 43 kDa. Moreover, metal ions, including 10 mM concentrations of the Ba2+, Mn2+, Zn2+, Fe3+, Cu2+, and Sr2+, demonstrated inhibitory effects on the L2 lipase activity by decreasing the lipase activity by 100, 18.8, 4.16, 18.86, 100, and 6.25 times. However, the 5 mM concentration of Ca2+ metal ions improved the lipase activity by 1.2 fold. Furthermore, the results after 30 min incubation of L2 lipase with pCMB, PMSF, EDTA, and DTT illustrated that L2 lipase retained 4, 5.3, 5.5, and 26.6% of its initial activity, respectively. The substrate specificity results also illlustrated relative lipase activities of 200, 66.66, 44, 40, 11.33, 9.3, and 13.33% towards sesame oil, coconut oil, rice bran oil, corn oil, sun floweroil, soybean oil, and canola oil, respectively, compared to olive oil. © The Author(s), under exclusive licence to Plant Science and Biodiversity Centre, Slovak Academy of Sciences (SAS), Institute of Zoology, Slovak Academy of Sciences (SAS), Institute of Molecular Biology, Slovak Academy of Sciences (SAS) 2024.